Pengembangan Peta Terintegrasi dan WebGis sebagai Media Informasi Spasial Nagari Limau Lunggo Kecamatan Lembang Jaya, Kabupaten Solok - Rehan Pramudiva Zikri; Dafid Kurniawan; Arif Rahman Fadilah; Khalisya Maulidya Arzila; Setiawati Setiawati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The availability of accurate and integrated spatial data is a crucial requirement in supporting administration and development planning at the Nagari level. Limau Lunggo Nagari, Lembang Jaya District, Solok Regency, previously did not have a comprehensively documented regional map, particularly regarding Jorong boundaries, land use and distribution of house numbers. This study aims to develop an integrated map and implement it in the form of a Web Geographic Information System (Web GIS) as a spatial information medium. The methods used include participatory data collection through interviews, discussions, and field observations, as well as spatial data processing using ArcGIS with reference to the Indonesian Topographic Map (RBI) and satellite imagery basecamp. The results of the study are in the form of three main maps, namely the jorong administrative boundary map, the land use map, and the distribution map of house numbers. The maps are presented in printed form as information signs and integrated into Google My Maps embedded on the official Nagari website. The implementation of Web GIS allows for interactive and easily accessible data presentation, thus supporting information transparency and spatial data-based decision-making at the Nagari level.